Analysis of Regulatory Quality, Interagency Coordination, and Institutional Capacity on the Effectiveness of Public Services in Jakarta - Loso Judijanto; Moh Gifari Sono; Wahyudin Wahyudin (Westscience Press, 2024)
This study examines the impact of regulatory quality, interagency coordination, and institutional capacity on the effectiveness of public services in Jakarta. Using a quantitative approach, data were collected from 100 respondents working in Jakarta’s public service sector. A Likert scale (1-5) questionnaire was employed to measure perceptions of the governance factors and service effectiveness, and the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that all three governance factors—regulatory quality, interagency coordination, and institutional capacity—significantly and positively affect public service effectiveness, with institutional capacity having the strongest influence. The findings highlight the importance of governance reforms aimed at improving regulatory frameworks, enhancing interagency collaboration, and strengthening institutional capacity to ensure efficient public service delivery in Jakarta. This research provides key insights for policymakers to optimize governance systems for better public sector performance.